The Household, Income and Labour Dynamics in Australia (HILDA) Survey: Wave 1 Weighting - Watson, N; Fry, T (Melbourne Institute of Applied Economic and Social Research, 2002)
This paper details the methodology used to calculate the weights for the Wave 1 sample of the Household, Income and Labour Dynamics in Australia (HILDA) Survey. The initial (or design) weights are derived from the probability of selecting the households into the sample. These household weights are initially adjusted according to information collected about all selected households (both responding and non-responding) and further adjusted so that weighted household estimates from the HILDA Survey match several known household-level benchmarks.
HILDA Project Technical Paper Series
Keywords: Surveys and Survey Methodology -- Survey response; Surveys and Survey Methodology -- Dataset cleaning and development; Surveys and Survey Methodology; Surveys and survey methodology; Surveys and Survey Methodology; Survey response; Dataset cleaning and development; Surveys and Survey Methodology